Work group report: perspectives in diagnosis and management of exercise-induced bronchoconstriction in athletes - Greiwe, J.; Cooke, A.; Nanda, A.; Epstein, S. Z.; Wasan, A. N.; Shepard II, K. V.; Capão-Filipe, M.; Nish, A.; Rubin, M.; Gregory, K. L.; Dass, K.; Blessing-Moore, J.; et al. (The Journal of Allergy and Clinical Immunology, 2020)
Exercise-induced bronchoconstriction, otherwise known as exercise-induced bronchoconstriction with asthma or without asthma, is an acute airway narrowing that occurs as a result of exercise and can occur in patients with asthma. A panel of members from the American Academy of Allergy, Asthma & Immunology Sports, Exercise, & Fitness Committee reviewed the diagnosis and management of exercise-induced bronchoconstriction in athletes of all skill levels including recreational athletes, high school and college athletes, and professional athletes. A special emphasis was placed on the recommendations and regulations set forth by professional athletic organizations after a detailed review of their collective bargaining agreements, substance abuse policies, antidoping program manuals, and the World Anti-Doping Agency antidoping code. The recommendations in this review are based on currently available evidence in addition to providing guidance for athletes of all skill levels as well as their treating physicians to better understand which pharmaceutical and nonpharmaceutical management options are appropriate as well as which medications are permitted or prohibited, and the proper documentation required to remain compliant.